2014
DOI: 10.18052/www.scipress.com/ilns.19.30
|View full text |Cite
|
Sign up to set email alerts
|

Media Optimization for Depolymerization of Alginate by <i>Pseudomonas aeruginosa</i> AG LSL-11

Abstract: An agar degrading bacterium Pseudomonas aeruginosa AG LSL-11 was acclimatized to alginate for the production of alginase. Production parameters such as pH, temperature, influence of simple carbohydrates and nitrogen sources, and effect of NaCl on growth and alginase production were carried out. Maximum growth was observed at pH 9.0 and 35 °C, while alginase was produced optimally at pH 9.0 and 30 °C. The alginase produced by Pseudomonas aeruginosa AG LSL-11 was inducible by alginate, and repressed by other sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Therefore, to sustain their exhausted growth, surviving cells might have degraded the alginate into oligosaccharides of respective constituents as a consumable carbon source using extracellular alginate lyase (Koti et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, to sustain their exhausted growth, surviving cells might have degraded the alginate into oligosaccharides of respective constituents as a consumable carbon source using extracellular alginate lyase (Koti et al, 2014 ).…”
Section: Resultsmentioning
confidence: 99%
“…These results also suggested that nutrients, including the carbon source, were available for sustainable growth and alginate production up to 150 h after which prolonged incubation led to a reduction in yields due to nutrient scarcity (Manresa et al, 1987). Therefore, to sustain their exhausted growth, surviving cells might have degraded the alginate into oligo-saccharides of respective constituents as a consumable carbon source using extracellular alginate lyase (Koti et al, 2014).…”
Section: Quantification Of Cell Growth and Alginate Biosynthesismentioning
confidence: 93%
“…Pseudomonas aeruginosa is causing septicemia, cystic fibrosis (CF), infections of the respiratory tract, burn wounds, urinary tract, and blood. The opportunistic pathogen P.aeruginosa secretes of alginate as a capsule-like polysaccharide, that has an im-portant role in evasion of host defenses, especially during the chronic pulmonary disease of patients with cystic fibrosis (20). Researchers have shown that alginate lyase therapy (inhibition) can decrease viscosity in cultures of clinical isolates and in CF sputum; dissociates biofilms from abiotic surfaces and enhances the phagocytosis and manslaughter of P.aeruginosa by human immune cells, and also improves the efficacy of various antibiotics.…”
mentioning
confidence: 99%